Acetylcholinesterase inhibitory activity, anti-inflammatory, and neuroprotective potential of Hippeastrum psittacinum (Ker Gawl.) herb (Amaryllidaceae). (November 2020) - Gasca, Cristian A.; Moreira, Natalia C.S.; de Almeida, Fernanda C.; Dutra Gomes, João V.; Castillo, Willian O.; Fagg, Christopher W.; Magalhães, Pérola O.; Fonseca-Bazzo, Yris M.; Sakamoto-Hojo, Elza; de Medeiros, Yanna K.; de Souza Borges, Warley; Silveira, Dâmaris
Abstract: Hippeastrum psittacinum, Amaryllidaceae, is used in traditional medicine as a purgative, aphrodisiac, and anticough remedy. The ethanol extract (EE) and alkaloid-rich fractions (ARF) from H. psittacinum bulbs were evaluated for their acetylcholinesterase (AChE) inhibition. The EE cytotoxic and anti-inflammatory effects in RAW 264.7 cells, and the neuroprotective and genotoxic activities in SH-SY5Y cells, were also estimated. Fifteen alkaloids were identified in the EE by gas chromatography–mass spectrometry. ARFs were less active for AChE inhibition than EE. The viability of both cell lines was higher than 70% with EE concentrations below 25 μg/mL. The EE decreased nitrite release in RAW cells stimulated with lipopolysaccharide, showing values of 83, 67, and 53% at 6.25, 12.5, and 25 μg/mL, respectively. Furthermore, the EE partially protected SH-SY5Y cells from hydrogen peroxide-mediated deleterious effects by approximately 50% at the same concentrations. The micronucleus assays showed that the extract caused chromosomal missegregation at concentrations above 12.5 μg/mL. The in silico analyses showed that some alkaloids presented properties of permeation of the blood-brain barrier and the intestine. Our findings present new evidence of the potential of H. psittacinum potential as an AChE inhibitor, as well as an anti-inflammatory and neuroprotective agent. Graphical abstract: Image 1 Highlights: The ethanol extract and alkaloid fractions from H. psittacinum bulbs inhibited AChE. H. psittacinum protected SH-SY5Y cells from hydrogen peroxide-induced neurotoxicity. H. psittacinum reduce nitrite release in a LPS-induced RAW 264.7 cell model. H. psittacinum is not genotoxic in SH-SY5Y cells in concentrations below 25 μg/mL.